A digital literary magazine to develop the critical thinking of students from modern languages program at universidad ECCI in a multilingual context (2017)
Within the arrival of the new worldwide context, literature has been one of the most useful tools in order to communicate with people. Also, to express the different ideals and thoughts of the different writers overseas. Most of them were writers in magazines and this one, being part of the human progress and being one of the first literary entertainments allowed the improvement of writing and reading. Along with the advancement of technology they permitted to the magazines being part of the digital world and being accessible to everyone. The purpose of this Digital Literary Magazine is to foster the features of critical thinking, reading and writing in the students and professors of Universidad ECCI and to show the different types of handwritten art and the skills that can being improved.